KOTRA Sebagai Upaya Diplomasi Publik Korea Selatan dalam Meningkatkan Kekuatan Ekonominya di Indonesia - Dwian, Jasmine Shafa; Sushanti, Sukma; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
The diplomatic relation between South Korea and Indonesia have existed for decades, resulting in many collaboration progressed in trade and investment that becomes an interesting topic for further research. This is supported with the establishment of KOTRA (Korea Trade Investment Promotion Agency) as the affiliate agency operated by MOTIE (Ministry of Trade, Investment and Energy). This process happened with the evolvement on the fast moving of globalization era and the revolution of science and technology resulting in the entrance of new era called as Information Age Era. In this era, there are new international actors that was emerging and KOTRA is the form on how the process of a country maximize new actors to contribute into strengthening their soft power. Although it’s not just new actors, but the varieties of new public diplomacy instruments was also emerging in the Information Age Era. KOTRA becomes as the representative of this particular process with the main duty to accelerate the economic development of South Korea and enhancing their economic strength with all the partner countries of KOTRA especially in Indonesia for this research. The result of this research showed there is a positive effect from the optimalization of KOTRA public diplomacy towards their trade and investment activity in Indonesia. To understand the process, this research will explain about KOTRA role using the concept of soft power and public diplomacy. This research will use explanatory-qualitative methodology that will use a secondary data sourced from books, journals, KOTRA digital report, KOTRA digital site and platform also any related and relevant news sources. Keywords : Affiliate Agency, KOTRA role, Public Diplomacy, Soft Power, South Korea